Battery cell and battery

By setting a glue coating layer in the separator of the lithium-ion battery and controlling the thickness ratio, the problem of short battery life caused by insufficient electrolyte residue is solved, the battery cycle performance and high temperature safety are improved, and the battery service life is extended.

CN119275489AActive Publication Date: 2025-01-07ZHUHAI COSMX POWER BATTERY CO LTD

Patent Information

Application Number
CN202411364626.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

During use, lithium-ion batteries have problems such as short life and fast battery capacity decay. Especially due to insufficient electrolyte residue, the ion bridge is broken, and the inability to effectively shuttle the positive and negative electrodes, which may cause safety accidents.

Method used

By providing a glue coating layer in the separator of the battery cell and controlling the thickness ratio of the glue coating layer in the first and second areas in the straight area, the electrolyte retention rate is improved, the distance between the positive and negative electrodes is shortened, and ion embedding is reduced. The length of the path that is released, thereby extending the cycle life of the battery.

Benefits of technology

It improves the battery's long cycle performance and high-temperature safety performance, extends the battery's service life, and reduces the risk of bridge breakage caused by insufficient electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275489A_ABST
    Figure CN119275489A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery cell and a battery comprising the same. The battery cell comprises a positive plate, a diaphragm and a negative plate, the diaphragm is located between the positive plate and the negative plate and comprises a base material and gluing layers, the gluing layers are located on the two sides of the base material or located on the side, close to the positive plate, of the base material, the battery cell comprises a straight area and a bent area, and the diaphragm comprises a first area and a second area corresponding to the straight area. The second area is an area where the diaphragm is overlapped with the projection of the positive plate, the first area is an area where the diaphragm is not overlapped with the projection of the positive plate, the thickness of the gluing layer in the first area is H1, the thickness of the gluing layer in the second area is H2, and the battery cell meets the following relational expression: 1 < H1 / H2 < = 10. The battery disclosed by the invention is high in cycling stability and good in high and low temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery cell and a battery comprising the battery cell. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in smart phones, tablet computers, power tools, energy storage, electric vehicles, etc. With the widespread application of lithium-ion batteries, consumers' requirements for the service life and application environment of lithium-ion batteries are constantly increasing, which requires lithium-ion batteries to have both high and low temperature performance and good cycle performance.

[0003] Currently, lithium-ion batteries have the problem of short lifespan during use. For example, the battery capacity decays rapidly after being used for a period of time. In the best case, the battery cannot be charged or discharged. In the worst case, serious safety accidents may occur, such as fire or even explosion. Summary of the invention

[0004] Research has found that the main reason for the battery cycle life problem is insufficient residual electrolyte during the cycle, which causes ion bridge failure at local locations in the battery, making it impossible for lithium ions to effectively shuttle between the positive and negative electrodes.

[0005] In order to overcome the above technical problems existing in the prior art, the present invention provides a battery cell and a battery comprising the battery cell. The battery cell of the present invention improves the retention rate of the electrolyte by controlling the thickness ratio of the glue layer in the flat area, and at the same time shortens the distance between the positive and negative electrodes, thereby improving the long cycle performance of the battery.

[0006] A first aspect of the present invention provides a battery cell, wherein the battery cell includes a positive electrode sheet, a separator and a negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator includes a substrate and a coating layer, the coating layer is located on both sides of the substrate or on the side of the substrate close to the positive electrode sheet, the battery cell includes a straight area and a bending area, the separator includes a first area and a second area corresponding to the straight area, the second area is the area where the projection of the separator overlaps with the positive electrode sheet, the first area is the area where the projection of the separator does not overlap with the positive electrode sheet, the thickness of the coating layer in the first area is H1, and the thickness of the coating layer in the second area is H2, then the battery cell satisfies the following relationship: 1

[0007] A second aspect of the present invention provides a battery, comprising the battery cell described in the first aspect of the present invention.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] ​By providing a coating layer at least on one side of the substrate of the diaphragm close to the positive electrode sheet, and by controlling the ratio of the thickness of the coating layer in the first area to the thickness of the coating layer in the second area in the straight area of ​​the battery cell, the electrolyte residue in the diaphragm can be increased, the electrolyte retention rate in the battery can be improved, and the distance between the positive and negative electrode sheets can be reduced, thereby shortening the path length of ion insertion and extraction, thereby improving the long cycle performance of the battery and extending the cycle life of the battery.

[0010] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a schematic structural diagram of an unwound battery cell of the present invention.

[0013] Figure 2 Shown is a schematic structural diagram of a battery with a wound cell according to the present invention.

[0014] Figure 3 Shown Figure 2 One of the schematic diagrams of the AA section.

[0015] Figure 4 Shown Figure 2 The second schematic diagram of the AA section.

[0016] Figure 5 Shown is a schematic diagram of the separator corresponding to the straight area of ​​the wound battery cell structure in the present invention.

[0017] Figure 6 Shown is a SEM image of the separator corresponding to the straight area of ​​the wound battery cell in the present invention.

[0018] Figure 7 Shown is a SEM image of the separator corresponding to the bending area of ​​the wound battery cell in the present invention. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.

[0020] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0021] A first aspect of the present invention provides a battery cell, wherein the battery cell includes a positive electrode sheet, a separator and a negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator includes a substrate and a coating layer, the coating layer is located on both sides of the substrate or on the side of the substrate close to the positive electrode sheet, the battery cell includes a straight area and a bending area, the separator includes a first area and a second area corresponding to the straight area, the second area is the area where the projection of the separator overlaps with the positive electrode sheet, the first area is the area where the projection of the separator does not overlap with the positive electrode sheet, the thickness of the coating layer in the first area is H1, and the thickness of the coating layer in the second area is H2, then the battery cell satisfies the following relationship: 1

[0022] The battery cell may satisfy: 1

[0023] In the present invention, the thickness of the coating layer is an average thickness, and the specific testing method is: in the SEM image of the diaphragm, within the range of 400 μm×500 μm, the average value of the thickness of the coating layer with a diameter of more than 2 μm is measured.

[0024] like Figure 1 As shown, the separator 1 is located between the positive electrode sheet 2 and the negative electrode sheet 3 , and the separator 1 includes a substrate 11 and a coating layer 12 . The coating layer 12 is located on both sides of the substrate 11 or on one side of the substrate 11 close to the positive electrode sheet 2 .

[0025] like Figure 2 As shown, the battery may include a height H, a width W, and a thickness T. It is understood that in the cell structure, the separator is located between the positive electrode sheet and the negative electrode sheet, and the separator serves to separate the positive and negative electrode sheets. The starting point of the cell is S, and S is the starting point position of the positive electrode sheet. At S, the positions of the positive electrode sheet, the separator, and the negative electrode sheet can be aligned (as shown in FIG. Figure 4 As shown, the positive electrode sheet and the negative electrode sheet at S are aligned), or they may not be aligned (as shown Figure 3 As shown, the positions of the positive electrode sheet and the negative electrode sheet at S are not aligned), that is, the starting positions of the positive electrode sheet and the negative electrode sheet can be the same or different.

[0026] In the present invention, the battery cell includes a bending area and a straight area, and the corresponding separator includes an area corresponding to the bending area of ​​the battery cell and an area corresponding to the straight area of ​​the battery cell. In the battery cell structure, the straight area is an unbent area, such as Figure 3 and Figure 4 ​​The area between the midline MN and the line OP is a straight area, and the straight area is an unbent area, such as Figure 3 and Figure 4 The area to the left of the center line MN and to the right of the line OP is a bending zone, where bending occurs.

[0027] In the present invention, in the height H direction of the battery core, the height of the diaphragm is greater than the height of the positive electrode sheet, such as Figure 5 As shown, in the height H direction of the battery cell, the projection of the diaphragm located in the first area 1111 on the positive electrode sheet 2 does not overlap with the positive electrode sheet 2 , and the projection of the diaphragm located in the second area 1112 on the positive electrode sheet 2 overlaps with the positive electrode sheet 2 .

[0028] The present invention provides a coating layer at least on one side of the substrate of the diaphragm close to the positive electrode sheet, and by controlling the ratio of the thickness of the coating layer in the first area to the thickness of the coating layer in the second area in the flat area, a "groove" capable of storing a certain amount of electrolyte can be formed in the flat area, thereby increasing the residual electrolyte in the diaphragm, improving the retention rate of the electrolyte in the battery, and thus overcoming the problem of bridge breaking caused by insufficient electrolyte. At the same time, the distance between the positive and negative electrode sheets can be reduced, thereby shortening the path length of ion insertion and extraction, thereby improving the long cycle performance of the battery and extending the cycle life of the battery.

[0029] In the present invention, by providing a coating layer at least on one side of the separator substrate close to the positive electrode sheet, and by controlling the ratio of the thickness of the coating layer in the first region to the thickness of the coating layer in the second region in the straight region, a more stable cycle performance than the battery in the prior art can be achieved. In order to further improve the effect, one or more of the technical features may be further optimized.

[0030] The coating layer may be located on both sides of the substrate or on a side of the substrate close to the positive electrode sheet.

[0031] In one example, the coating layer is located on a side of the substrate close to the positive electrode sheet.

[0032] like Figure 1As shown, the coating layer 12 is located on the side of the substrate 11 close to the positive electrode sheet 2, that is, the positive electrode sheet 2 is in direct contact with the coating layer 12, and the side of the substrate 11 away from the positive electrode sheet 2 (that is, the side close to the negative electrode sheet 3) can be in direct contact with the negative electrode sheet 3. At this time, the battery can still solve the problem of shortened battery cycle life due to insufficient residual electrolyte, and achieve the effect of improving battery cycle stability and extending battery cycle life. In addition, since the substrate of the diaphragm close to the negative electrode sheet is in direct contact with the negative electrode sheet, the possibility of diaphragm channel blockage can be reduced, making the ion transmission of the diaphragm on the negative electrode side smoother, and at the same time, it can have better adhesion with the negative electrode. In addition, since only one side of the substrate of the diaphragm is coated with a coating layer, the cost of the battery can be reduced.

[0033] In one example, the battery cell satisfies the following relationship: 1.5≤H1 / H2≤5.

[0034] In one example, H1 is 0.5 μm-5 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm).

[0035] In one example, H2 is 0.2 μm-3 μm (eg, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm).

[0036] In one example, the battery cell satisfies the following relationship: 1

[0037] In one example, the thermal shrinkage rate of the diaphragm at 130°C is ≤5%. The test method for the thermal shrinkage rate is: take a 15cm*15cm area of ​​the diaphragm sample, pierce two holes with a diameter of 0.5mm at a distance of 10cm along the length direction of the diaphragm, and bake the sample in an oven at 130±2°C for 1h. The spacing between the two holes before baking is L1, and the spacing between the two holes after baking is L2. The thermal shrinkage rate = (L1-L2) / L1*100%. Controlling the thermal shrinkage rate of the diaphragm within the above range can effectively block the contact between the positive and negative electrodes of the battery when the battery is placed in a high temperature environment, reduce the risk of short circuit between the positive and negative electrodes, and thus improve the high temperature safety performance of the battery.

[0038] In one example, based on the area of ​​the flat area, the coverage area of ​​the adhesive layer located in the flat area accounts for B% of 10%-40% (for example, 10%, 15%, 20%, 25%, 30%, 35% or 40%) (see Figure 6 ​). Research has found that the cause of the battery cycle life problem also includes the swelling of the coating layer on the surface of the diaphragm with the electrolyte, which blocks the diaphragm channel and causes the diaphragm to be unable to smoothly transfer ions, resulting in serious capacity decay in the later stages of the cycle. Based on this, by controlling the coverage area ratio of the coating layer in the flat area, the swelling of the coating layer on the surface of the diaphragm with the battery and the blocking of the diaphragm channel can be improved, so that ion transfer can proceed smoothly, thereby improving the battery cycle performance.

[0039] In one example, based on the area of ​​the bending zone, the coverage area of ​​the coating layer located in the bending zone accounts for A% of 5%-30% (for example, 5%, 10%, 15%, 20%, 25% or 30%) (see Figure 7 ).

[0040] Research has found that the cause of the battery cycle life problem also includes the easy lithium deposition in the bending zone, which will cause the battery cycle capacity to decay, and then affect the battery's cycle performance and safety performance. Based on this, by controlling the coverage area ratio of the glue layer in the bending zone, the lithium deposition problem in the bending zone can be improved, thereby improving the battery's safety performance. At the same time, it can also improve the situation where the glue layer on the surface of the diaphragm swells with the battery and blocks the diaphragm channel, so that ion transfer can proceed smoothly, thereby improving the battery's cycle performance.

[0041] In one example, based on the area of ​​the diaphragm, the coverage area of ​​the coating layer is 5%-40% (eg, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%).

[0042] In one example, based on the area of ​​the bending zone, the coverage area of ​​the adhesive layer in the bending zone accounts for A% of 5%-30%, and based on the area of ​​the straight zone, the coverage area of ​​the adhesive layer in the straight zone accounts for B% of 10%-40%, and based on the area of ​​the diaphragm, the coverage area of ​​the adhesive layer accounts for 5%-40%. By simultaneously controlling the coverage area ratio of the adhesive layer in the bending zone, the coverage area ratio of the adhesive layer in the straight zone, and the coverage area ratio of the adhesive layer in the diaphragm, the situation in which the adhesive layer on the surface of the diaphragm swells with the battery and blocks the diaphragm channel can be further improved, so that ion transmission can proceed smoothly, thereby improving the cycle performance of the battery.

[0043] In one example, if Figure 1 As shown, the coating layer 12 includes a polymer 121, and the polymer 121 includes primary particles and secondary particles, wherein the secondary particles are formed by stacking primary particles.

[0044] In one example, the median particle size Dv50 of the primary particles is 100 nm-300 nm (eg, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, or 300 nm).

[0045] In one example, the median particle size Dv50 of the secondary particles is 0.1 μm-100 μm (e.g., 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm).

[0046] In one example, the median particle size Dv50 of the secondary particles is 1 μm-50 μm.

[0047] In the present invention, the median particle size Dv50 can be obtained by testing with a laser particle size analyzer.

[0048] In one example, the average particle size of the primary particles is 100 nm-300 nm (eg, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, or 300 nm).

[0049] In one example, the average particle size of the secondary particles is 0.1 μm-100 μm (e.g., 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm).

[0050] In one example, the average particle size of the secondary particles is 1 μm-50 μm.

[0051] In the present invention, the average particle size can be obtained by testing in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), the surface of the porous layer is observed at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the average particle size, a square or rectangle with the smallest area that completely surrounds one particle is drawn on the obtained image, that is, a square or rectangle in which the end of the particle is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the particle size, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the particle size. For any 81 particles, the particle size is measured, and the number average is set as the average particle size. It should be noted that when more than 81 particles are observed in the captured image, the number average of any 81 particle sizes in the image is set as the average particle size. When 81 particles are not observed in the image, multiple images are captured and the number average of the total 81 particle sizes is set as the average particle size.

[0052] In one example, the polymer includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyacrylonitrile, polymethyl methacrylate, and polyacrylic acid.

[0053] In one example, based on the total weight of the coating layer, the weight content of the polymer is 80wt%-95wt% (e.g., 80wt%, 82wt%, 85wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt% or 95wt%).

[0054] In one example, based on the total weight of the coating layer, the weight content of the polymer is 85 wt %-94 wt %.

[0055] In one example, the coating layer includes a first binder and a thickener.

[0056] In one example, based on the total weight of the coating layer, the weight content of the first binder is 1wt%-15wt% (for example, 1wt%, 3wt%, 5wt%, 7wt%, 9wt%, 10wt%, 11wt%, 13wt% or 15wt%), and the weight content of the thickener is 1wt%-5wt% (for example, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%).

[0057] In one example, the coating layer includes a first binder and a thickener. Based on the total weight of the coating layer, the weight content of the first binder is 3wt%-12wt%, and the weight content of the thickener is 1.5wt%-4.5wt%.

[0058] In one example, the first binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate and carboxyethyl cellulose.

[0059] In one example, the thickener includes one or more of carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), and lithium carboxymethyl cellulose (CMC-Li).

[0060] In one example, the substrate includes one or more of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyparaphenylene, polynaphthalene, polyimide, polyamide, aramid, and polyparaphenylenebenzodithiazole.

[0061] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent and a positive electrode binder.

[0062] In one example, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active substance, the positive electrode active substance includes a ternary material that has been or has not been subjected to a doping and coating treatment, or lithium iron phosphate that has been or has not been subjected to a doping and coating treatment, wherein the doped elements include one or more of Al, Mg, Mn, Cr, Ti, V and Zr.

[0063] In one example, the median particle size Dv50 of the positive electrode active material is 0.3 μm-5 μm (eg, 0.3 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm).

[0064] In one example, the average particle size of the primary particles is D1, the average particle size of the secondary particles is D2, and the median particle size Dv50 of the positive electrode active material is D3. Then, the battery cell satisfies the following relationship: 0.1≤D1 / D3≤1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), and / or, 1≤D2 / D3≤20 (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20). Controlling the average particle size D1 of the primary particles to be less than or equal to the median particle size D3 of the positive electrode active material can make the primary particles embedded between the particles of the positive electrode active material, thereby improving the bonding force between the coating layer and the positive electrode active material layer through the riveting force, and controlling the average particle size D2 of the secondary particles to be greater than or equal to the median particle size D3 of the positive electrode active material can make the secondary particles incompletely embedded between the particles of the positive electrode active material, thereby increasing the contact area between the coating layer and the positive electrode active material layer, and improving the bonding force between the coating layer and the positive electrode active material layer through the chemical bond between the coating layer and the positive electrode active material layer. By improving the bonding force between the coating layer and the positive electrode active material layer, the interface stability between the diaphragm and the positive electrode sheet can be improved, thereby reducing the side effects on the positive electrode side and improving the long cycle performance of the battery.

[0065] In one example, the battery cell satisfies the following relationship: 0.2≤D1 / D3≤0.8, and / or, 1.2≤D2 / D3≤15.

[0066] In one example, the average particle size of the primary particles is 100nm-300nm, and the average particle size of the secondary particles is 0.1μm-100μm, and the median particle size Dv50 of the positive electrode active material is 0.3μm-5μm, and the average particle size of the primary particles is D1, the average particle size of the secondary particles is D2, and the median particle size Dv50 of the positive electrode active material is D3, then the battery cell satisfies the following relationship: 0.1≤D1 / D3≤1, and / or, 1≤D2 / D3≤20.

[0067] In one example, the positive electrode conductive agent includes one or more of acetylene black, Ketjen black, carbon fiber, carbon nanotube and graphene.

[0068] In one example, the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyimide, polyacrylic acid, and polyacrylonitrile.

[0069] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 85wt%-99wt% (for example, 85wt%, 87wt%, 90wt%, 92wt%, 95wt%, 97wt% or 99wt%), the weight content of the positive electrode conductor is 0.5wt%-8wt% (for example, 0.5wt%, 1wt%, 3wt%, 5wt% or 8wt%), and the weight content of the binder is 0.5wt%-7wt% (for example, 0.5wt%, 1wt%, 3wt%, 5wt% or 7wt%).

[0070] In one example, the positive electrode current collector includes one or more of aluminum foil and composite aluminum foil.

[0071] In one example, the diaphragm 1 includes a heat-resistant layer 13 , and the heat-resistant layer 13 is located between the substrate 11 and the adhesive layer 12 .

[0072] like Figure 1 As shown, the separator 1 includes a substrate 11 and a glue layer 12 located on a side of the substrate 11 close to the positive electrode sheet 2, and the heat-resistant layer 13 is located between the substrate 11 and the glue layer 12. It can be understood that the glue layer 12 and the heat-resistant layer 13 are included between the substrate 11 and the positive electrode sheet 2, wherein the glue layer 12 is in direct contact with the positive electrode sheet 2, and the substrate 11 is in direct contact with the negative electrode sheet 3.

[0073] In one example, the heat-resistant layer includes heat-resistant particles, and the median particle size Dv50 of the heat-resistant particles is 0.5 μm-2 μm (eg, 0.5 μm, 1 μm, 1.5 μm, or 2 μm).

[0074] In one example, the heat-resistant particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and nickel oxide. By controlling the specific selection of heat-resistant particles, the heat resistance of the separator can be controlled, so that the battery can still block the contact between the positive and negative electrodes at high temperatures, thereby improving the high-temperature safety performance of the battery.

[0075] In one example, the heat-resistant layer includes a second binder.

[0076] In one example, the second binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate and carboxyethyl cellulose.

[0077] In one example, based on the total weight of the heat-resistant layer, the weight content of the heat-resistant particles is 50wt%-99wt% (for example, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or 99wt%), and the weight content of the second binder is 1wt-50wt% (for example, 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%).

[0078] In one example, based on the total weight of the heat-resistant layer, the weight content of the heat-resistant particles is 80wt%-97wt%, and the weight content of the second binder is 3wt%-20wt%.

[0079] In one example, the adhesion between the separator and the positive electrode sheet is 2N / m-10N / m (e.g., 2N / m, 3N / m, 4N / m, 5N / m, 6N / m, 7N / m, 8N / m, 9N / m or 10N / m).

[0080] In one example, the coating layer in the diaphragm is located on the side of the substrate close to the positive electrode sheet, the substrate in the diaphragm is in direct contact with the negative electrode sheet, and the adhesion force between the diaphragm and the negative electrode sheet is 0.5N / m-5N / m (for example, 0.5N / m, 1N / m, 2N / m, 3N / m, 4N / m or 5N / m). By applying ultra-high pressure to the wound core, specifically pressing the core under a pressure of 3MPa-10MPa (for example, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa or 10MPa) for 1min-20min (for example, 1min, 3min, 5min, 8min, 10min, 13min, 15min, 18min or 20min), part of the negative electrode active material (the negative electrode active material in direct contact with the substrate in the diaphragm) is embedded in the diaphragm (substrate) under ultra-high pressure, so that the negative electrode sheet and the diaphragm have a certain adhesion force, ensuring the interface stability of the diaphragm and the negative electrode sheet, so that the battery has good long cycle performance.

[0081] When the substrate in the diaphragm is in direct contact with the negative electrode sheet, although there is no glue coating layer between the diaphragm and the negative electrode sheet, the diaphragm (substrate) and the negative electrode sheet can still have an adhesion force within the above range, thereby ensuring the interface stability between the diaphragm and the negative electrode sheet and improving the long cycle performance of the battery.

[0082] A second aspect of the present invention provides a battery, comprising the battery cell described in the first aspect of the present invention.

[0083] In one example, the battery includes an electrolyte.

[0084] In one example, the electrolyte includes ethylene carbonate and / or vinylene carbonate. Based on the total weight of the electrolyte, the weight content of vinylene carbonate is Cwt%, and the weight content of ethylene carbonate is Dwt%. Then the battery cell satisfies: 0.001≤C / (B / A)≤0.1, and / or, 1≤D / C≤10.

[0085] Research has found that the causes of battery cycle life problems also include excessive swelling of the electrolyte design and the diaphragm glue, which leads to serious diaphragm pore blockage; in addition, lithium precipitation in the bending zone is also an important factor that causes the battery cycle capacity to decay, thereby affecting the battery cycle performance. Based on this, by controlling the relationship between the coverage area ratio of the glue layer in the straight area, the coverage area ratio of the glue layer in the bending area, and the weight content of vinyl carbonate in the electrolyte, and / or controlling the weight content ratio of vinyl carbonate and vinyl carbonate in the electrolyte, the swelling effect of the electrolyte on the glue layer in the diaphragm can be reduced, and the lithium precipitation problem in the bending area can be improved, thereby improving the battery's cycle performance and safety performance.

[0086] In one example, the electrolyte includes ethylene carbonate and vinylene carbonate. Based on the total weight of the electrolyte, the weight content of vinylene carbonate is Cwt%, and the weight content of ethylene carbonate is Dwt%. Then the battery satisfies: 0.001≤C / (100*(B / A))≤0.1, and / or, 1≤D / C≤10.

[0087] In one embodiment, Cwt% is 0.1wt%-10wt% (for example, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%). When the content of vinylene carbonate (VC) in the electrolyte is less than 0.1wt%, the VC content is too low, resulting in slightly poor electrolyte kinetics, affecting the low temperature performance of the battery; when the VC content in the electrolyte is greater than 10wt%, the VC content is too high, resulting in excessive swelling of the polymer in the diaphragm coating layer, thereby increasing the coverage of the diaphragm coating layer, affecting the lithium ion transmission in the diaphragm, and affecting the long cycle performance of the battery.

[0088] In one example, C wt % is 1 wt % to 8 wt %.

[0089] In one example, D wt % is 5 wt %-25 wt % (eg, 5 wt %, 10 wt %, 15 wt %, 20 wt % or 25 wt %).

[0090] In one example, Dwt% is 7wt%-20wt%.

[0091] In one example, based on the area of ​​the bending zone, the coverage area of ​​the glue layer located in the bending zone accounts for A% of 5%-30%, and based on the area of ​​the straight zone, the coverage area of ​​the glue layer located in the straight zone accounts for B% of 10%-40%, Cwt% is 0.1wt%-10wt%, and Dwt% is 5wt-25wt%, and the battery satisfies: 0.001≤C / (100*(B / A))≤0.1, and / or, 1≤D / C≤10.

[0092] In one example, the electrolyte includes lithium salt, EMC, EA and LIFSi.

[0093] In one example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.

[0094] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 1wt%-20wt% (for example, 1wt%, 5wt%, 10wt%, 15wt% or 20wt%), the weight content of the EMC is 10wt%-70wt% (for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt% or 70wt%), the weight content of the EA is 10wt%-70wt% (for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt% or 70wt%), and the weight content of the LIFSi is 1wt%-20wt% (for example, 1wt%, 5wt%, 10wt%, 15wt% or 20wt%).

[0095] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 5wt%-15wt%, the weight content of the EMC is 15wt%-50wt%, the weight content of the EA is 15wt%-50wt%, and the weight content of the LIFSi is 5wt%-15wt%.

[0096] In one example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder.

[0097] In one example, the negative electrode active material includes one or more of graphite, hard carbon, SiOx / C and Si / C graphite composite materials.

[0098] In one example, the graphite includes one or more of artificial graphite and natural graphite.

[0099] In one example, the negative electrode conductive agent includes one or more of conductive carbon black (SP), acetylene black, Ketjen black, carbon fiber, carbon nanotube, and graphene.

[0100] In one example, the carbon nanotubes include one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes.

[0101] In one example, the negative electrode binder includes one or more of styrene-butadiene rubber (SBR), PAA, sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li), PVDF and PTFE.

[0102] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 80wt%-99wt% (for example, 80wt%, 85wt%, 90wt%, 95wt% or 99wt%), the weight content of the negative electrode conductor is 0.5wt%-10wt% (for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%), and the weight content of the negative electrode binder is 0.5wt%-10wt% (for example, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%).

[0103] In one example, the battery is a lithium-ion battery.

[0104] In one example, the battery is a lithium-ion secondary battery.

[0105] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0106] The following examples are provided to illustrate the batteries of the present invention.

[0107] Example 1

[0108] (1) Preparation of positive electrode

[0109] The positive electrode active material (lithium iron phosphate (LFP) doped with titanium and vanadium), the positive electrode binder (polyvinylidene fluoride (PVDF)), and the positive electrode conductor (acetylene black) are mixed in a weight ratio of 96.5:1.5:2.0, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the surface of both sides of an aluminum foil with a thickness of 10 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients (95°C±5°C, 100°C±5°C, 103°C±5°C, 100°C±5°C, 95°C±5°C), and then dried in an oven at 120°C for 8 hours, and then rolled and cut to obtain the desired positive electrode sheet.

[0110] (2) Preparation of negative electrode sheet

[0111] The negative electrode active material (artificial graphite), the negative electrode conductive agent (including 0.2 parts by weight of single-walled carbon nanotubes (SWCNT) and 1 part by weight of conductive carbon black (SP)), and the negative electrode binder (including 1 part by weight of sodium carboxymethyl cellulose (CMC-Na) and 2.5 parts by weight of styrene-butadiene rubber (SBR)) are mixed in a weight ratio of 95.3:1.2:3.5, and a slurry is prepared by a wet process (water is added to the mixture formed by the above mixing, and stirred under the action of a vacuum stirrer until the mixture becomes a negative electrode slurry with uniform fluidity), and the slurry is coated on the surfaces of both sides of the negative electrode collector (copper foil), and the negative electrode sheet is obtained by drying (temperature: 85°C, time: 5h), rolling and die-cutting.

[0112] (3) Preparation of electrolyte

[0113] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), 36 parts by weight of ethyl methyl carbonate (EMC), 27 parts by weight of ethyl acetate (EA), and 13.5 parts by weight of ethylene carbonate (EC) were mixed to obtain a mixed solution 1, 4.5 parts by weight of VC were added to the mixed solution 1 to obtain a mixed solution 2, 6.5 parts by weight of LiFSi and 12.5 parts by weight of lithium hexafluorophosphate were slowly added to the mixed solution 2, and the mixture was stirred to obtain a non-aqueous electrolyte.

[0114] (4) Preparation of diaphragm

[0115] Mix the heat-resistant particles (aluminum oxide, 95 parts by weight) and the second binder (poly(meth)acrylic acid, 5 parts by weight), which is referred to as solution A;

[0116] A polymer (polyvinylidene fluoride-hexafluoropropylene copolymer, 92 parts by weight), a first binder (poly(meth)acrylic acid, 4 parts by weight), and a thickener (sodium carboxymethyl cellulose, 4 parts by weight) were mixed and recorded as solution B;

[0117] Solution A was coated on one side of a substrate (PE) with a thickness of 7 μm by using a gravure roller, and after drying, a separator with a heat-resistant layer of 2 μm was obtained, which was recorded as separator C;

[0118] Solution B was sprayed on the heat-resistant layer side of membrane C, and after drying, a membrane with a 2μm heat-resistant layer and a 2um adhesive layer was obtained to obtain membrane D; the membrane had a heat-resistant layer and an adhesive layer on one side of the substrate, the heat-resistant layer was located between the substrate and the adhesive layer, and the other side was not coated with the heat-resistant layer and the adhesive layer.

[0119] (5) Preparation of lithium-ion batteries

[0120] The positive electrode sheet of step (1), the separator of step (4), and the negative electrode sheet of step (2) are wound to obtain a bare cell without liquid injection, wherein the adhesive layer in the separator is in direct contact with the positive electrode sheet, and the substrate (the side not coated with the heat-resistant layer and the adhesive layer) is in direct contact with the negative electrode sheet, and 5MPa is applied to the wound core for 10min; the bare cell is placed in an outer packaging foil, and the electrolyte of step (3) is injected into the dried bare cell. After vacuum packaging, standing, formation, shaping, sorting and other processes, the desired lithium-ion battery is obtained.

[0121] Example 2

[0122] The same method is carried out as in Example 1, except that the values ​​of the parameters are changed. For details, see Table 1-1 and Table 1-2.

[0123] Example 3

[0124] The same method is carried out as in Example 1, except that the values ​​of the parameters are changed. For details, see Table 1-1 and Table 1-2.

[0125] Example 4 Group

[0126] This group of examples is used to illustrate the effects of changing H1 / H2.

[0127] This example group is carried out with reference to Example 1, except that H1 / H2 is changed, see Table 1-1 and Table 1-2 for details.

[0128] Example 5 Group

[0129] This group of embodiments is used to illustrate the impact of changing the coverage area ratio of the adhesive layer.

[0130] This embodiment group is carried out with reference to the embodiment 1, except that the coverage area ratio of the adhesive layer is changed, see Table 1-1 and Table 1-2 for details.

[0131] Example 6 Group

[0132] This group of examples is used to illustrate the effect of changing the weight content of the polymer in the coating layer.

[0133] This example group was carried out with reference to Example 1, except that the weight content of the polymer in the coating layer was changed, as shown in Table 1-1 and Table 1-2 for details.

[0134] Example 7 Group

[0135] This group of embodiments is used to illustrate the effects of changing D1 and / or D2 and / or D3.

[0136] This embodiment group is carried out with reference to embodiment 1, except that D1 and / or D2 and / or D3 are changed, see Table 1-1 and Table 1-2 for details.

[0137] Example 8 Group

[0138] This group of examples is used to illustrate the effect of changing Cwt%.

[0139] This example group was carried out with reference to Example 1, except that Cwt% was changed. For details, see Table 1-1 and Table 1-2.

[0140] Example 9 Group

[0141] This group of examples is used to illustrate the effect of changing Dwt%.

[0142] This example group was carried out with reference to Example 1, except that Dwt% was changed. For details, see Table 1-1 and Table 1-2.

[0143] Example 10 Group

[0144] This group of examples is used to illustrate the impact of changing C / (100*(B / A)).

[0145] This example group was carried out with reference to Example 1, except that C / (100*(B / A)) was changed, see Table 1-1 and Table 1-2 for details.

[0146] Embodiment 11

[0147] The method is carried out in accordance with Example 1, except that both sides of the substrate of the diaphragm are coated with a heat-resistant layer and a rubber coating layer, as shown in Tables 1-1 and 1-2.

[0148] Comparative Example 1

[0149] The same method is carried out as in Example 1, except that no adhesive layer is applied. For details, see Table 1-1 and Table 1-2.

[0150] Comparative Example 2

[0151] The same procedure is carried out as in Example 1, except that H1 and / or H2 are changed to make H1 / H2>10. For details, see Table 1-1 and Table 1-2.

[0152] Comparative Example 3

[0153] The same procedure is carried out as in Example 1, except that H1 and / or H2 are changed to make H1 / H2 < 1. For details, see Table 1-1 and Table 1-2.

[0154] Comparative Example 4

[0155] The same procedure is carried out as in Example 1, except that H1 and / or H2 are changed to make H1 / H2=1. For details, see Table 1-1 and Table 1-2.

[0156] Table 1-1

[0157]

[0158]

[0159]

[0160] * indicates the same as in Example 1; - indicates absence.

[0161] Table 1-2

[0162]

[0163]

[0164]

[0165] *Same as Example 1;

[0166] - means it does not exist.

[0167] Test Case

[0168] The lithium ion batteries obtained in the embodiments and comparative examples were tested as follows:

[0169] (1) -20℃ cycle test

[0170] The lithium-ion battery was placed in a (-20±2)℃ environment and left to stand for 2-3 hours. When the battery reached (25±2)℃, the battery was charged at 1C constant current with a cutoff current of 0.05C. After the battery was fully charged, it was left for 5 minutes and then discharged at 1C constant current to a cutoff voltage of 3.0V. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q. When the cycle reached 10 times, the last discharge capacity Q1 of the battery was recorded. The capacity retention rate (%) = Q1 / Q×100%. The results are recorded in Table 2.

[0171] (2) 25℃ cycle test

[0172] The lithium-ion battery was placed in a (25±2)℃ environment and left to stand for 2-3 hours. When the battery body reached (25±2)℃, the battery was charged at 3C constant current with a cut-off current of 0.05C. After the battery was fully charged, it was left for 5 minutes and then discharged at 3C constant current to a cut-off voltage of 3.0V. The highest discharge capacity of the first three cycles was recorded as the initial capacity Q. When the cycle reached 1000 times, the last discharge capacity Q1 of the battery was recorded. The capacity retention rate (%) = Q1 / Q×100%. The results are recorded in Table 2.

[0173] (3) 130℃ thermal shock test

[0174] The lithium-ion battery was heated in a convection air box at a starting temperature of (25±3)°C, a temperature change rate of (5±2)°C / min, and the temperature was raised to (130±2)°C. The test was terminated after maintaining for 60 minutes, and the battery status was recorded. There were 15 batteries in each sample. If no explosion and / or fire occurred, it was indicated as "passed", and if explosion or fire occurred, it was indicated as "failed". The result was expressed as "number of passes / 15", for example, "15 / 15" means that all batteries passed, and "10 / 15" means that 10 batteries out of 15 batteries failed. The specific results are recorded in Table 2.

[0175] Table 2

[0176]

[0177]

[0178] a When the battery prepared in comparative example 1 was subjected to a 25°C cycle capacity retention rate test, the cycle capacity retention rate of the battery dropped sharply to 70% after 500 cycles, and then the cycle capacity retention rate of the battery dropped rapidly, and the 1000-cycle test could not be completed.

[0179] b When the battery prepared in comparative example 3 was subjected to a 25°C cycle capacity retention rate test, the cycle capacity retention rate of the battery dropped sharply to 70% after 300 cycles, and then the cycle capacity retention rate of the battery dropped rapidly and could not complete the 1000-cycle test.

[0180] It can be seen from Table 2 that the comparative examples and the embodiments show that by providing a coating layer at least on one side of the substrate of the diaphragm close to the positive electrode sheet, and by controlling the ratio of the thickness of the coating layer in the first area to the thickness of the coating layer in the second area in the straight area, the cycle stability and safety performance of the battery are improved, and the life of the battery is extended.

[0181] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery cell, characterized in that: The battery cell includes a positive electrode sheet, a separator and a negative electrode sheet, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator includes a substrate and a coating layer, the coating layer is located on both sides of the substrate or on the side of the substrate close to the positive electrode sheet, the battery cell includes a straight area and a bending area, the separator includes a first area and a second area corresponding to the straight area, the second area is the area where the separator overlaps with the projection of the positive electrode sheet, the first area is the area where the separator does not overlap with the projection of the positive electrode sheet, the thickness of the coating layer in the first area is H1, and the thickness of the coating layer in the second area is H2, then the battery cell satisfies the following relationship: 1<H1 / H2≤10.

2. The battery cell according to claim 1, wherein: The battery cell satisfies the following relationship: 1.5≤H1 / H2≤5; and / or, H1 is 0.5 μm-5 μm; and / or, H2 is 0.2 μm-3 μm; And / or, the coating layer is located on a side of the substrate close to the positive electrode sheet; And / or, the thermal shrinkage rate of the separator at 130° C. is ≤5%.

3. The battery cell according to claim 2, wherein: Based on the area of ​​the diaphragm, the coverage area of ​​the coating layer accounts for 5%-40%; And / or, based on the area of ​​the bending zone, the coverage area of ​​the adhesive layer located in the bending zone accounts for A% of 5%-30%; And / or, based on the area of ​​the flat area, the coverage area of ​​the rubber coating layer located in the flat area accounts for B% of 10%-40%.

4. The battery cell according to any one of claims 1 to 3, wherein: The coating layer includes a polymer, and the polymer includes primary particles and secondary particles; And / or, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active substance, the positive electrode active substance includes a ternary material that has been or has not been subjected to a doping and coating treatment, or lithium iron phosphate that has been or has not been subjected to a doping and coating treatment, wherein the doped elements include one or more of Al, Mg, Mn, Cr, Ti, V and Zr.

5. The battery cell according to claim 4, wherein: The average particle size of the primary particles is D1, the average particle size of the secondary particles is D2, and the median particle size Dv50 of the positive electrode active material is D3. Then, the battery cell satisfies the following relationship: 0.1≤D1 / D3≤1, and / or, 1≤D2 / D3≤20; and / or, based on the total weight of the coating layer, the weight content of the polymer is 80wt%-95wt%; and / or, the polymer comprises one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyimide, polyacrylonitrile, polymethyl methacrylate and polyacrylic acid; And / or, the average particle size of the primary particles is 100nm-300nm; and / or, the average particle size of the secondary particles is 0.1 μm-100 μm; And / or, the median particle size Dv50 of the positive electrode active material is 0.3 μm-5 μm.

6. The battery cell according to any one of claims 1 to 3, wherein: The diaphragm comprises a heat-resistant layer, and the heat-resistant layer is located between the substrate and the rubber coating layer; Preferably, the heat-resistant layer comprises heat-resistant particles, and the median particle size Dv50 of the heat-resistant particles is 0.5 μm-2 μm; Preferably, the heat-resistant particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide and nickel oxide.

7. The battery cell according to claim 6, wherein: The coating layer comprises a first binder and a thickener, and based on the total weight of the coating layer, the weight content of the first binder is 1wt%-15wt%, and the weight content of the thickener is 1wt%-5wt%; And / or, the heat-resistant layer comprises a second binder, and based on the total weight of the heat-resistant layer, the weight content of the heat-resistant particles is 50wt%-99wt%, and the weight content of the second binder is 1wt-50wt%.

8. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 7.

9. The battery according to claim 8, wherein The battery includes an electrolyte, and the electrolyte includes ethylene carbonate and / or vinylene carbonate. Based on the total weight of the electrolyte, the weight content of the vinylene carbonate is Cwt%, and the weight content of the ethylene carbonate is Dwt%. Then the battery satisfies: 0.001≤C / (100*(B / A))≤0.1, and / or, 1≤D / C≤10.

10. The battery according to claim 9, wherein The electrolyte includes ethylene carbonate and vinylene carbonate; and / or, Cwt% is 0.1wt%-10wt%; And / or, Dwt% is 5wt%-25wt%.

Citation Information

Patent Citations

  • Battery

    CN114024099A

  • Winding type battery cell and electrochemical device

    CN117790928A

  • Battery cell and secondary battery

    CN219267840U

  • battery

    WO2023072110A1

  • Lithium ion battery separator

    WO2023093789A1

Cited By

  • Winding battery cell and electrochemical device comprising winding battery cell

    CN120376770A

  • A wound battery cell and an electrochemical device comprising the wound battery cell

    CN120376770B